Persiapan Masa Nifas Dan Asi Eksklusif Melalui Edukasi Dan Hipnobreasfeeding Pada Kelas Ibu Hamil - Adinda Putri Sari Dewi; Sumarni, Sumarni; Mutoharoh, Siti (STIKes Ibnu Sina Ajibarang, 2023)
Ayah Village is one of the villages in Ayah District, located near the beach. Based on data, exclusive breastfeeding coverage in Ayah's village from January-May 2022 is less than the target of 75%. This is caused by the lack of information regarding exclusive breastfeeding, irregularities in complying with ANC schedules, and less strategic placement of posyandu locations. Apart from that, the two posyandu do not routinely hold classes for pregnant women. The aim of this community service is to prepare for the postpartum period and exclusive breastfeeding through education and Hypnobreastfeeding in the Pregnant Women's Class in my father's village. The community service method is by screening 10 pregnant TM III people according to the criteria to be included in the pregnant women class. Then provide education and Hypnobreastfeeding to prepare for the postpartum and breastfeeding period. After that, an evaluation was carried out to convey the obstacles found when providing service implementation as well as program follow-up plans. The results of the activity showed that after this activity the majority of mothers had good knowledge about preparation for the postpartum period and breastfeeding. This community service activity has been achieved by adding information about education during the postpartum period and hypnobreasfeeding